Abdominal aortic aneurysm and horseshoe kidney – open surgical repair: A case report - Tomić, Aleksandar; Marjanović, Ivan; Sekulić, Dragan (Vojnosanitetski pregled, 2021)
Introduction. Horseshoe kidney (HSK) is a congenital anomaly of embryonic kidneys, which occurs in early gestation when both kidneys are in close proximity. This happens as a result of abnormal migration of nephrogenic cells. The presence of HSK may complicate an anterior approach to reconstructive surgery of the aorta and iliac vessels because the isthmus of the HSK lies across the aorta. HSK is often associated with anomalous renal vessels. Case report. A 71-year-old female patient was admitted with an abdominal aortic aneurysm, 50 mm in diameter, and HSK, and multiple aberrant renal vessels with subocluded upper left renal artery as seen on the multidetector computed tomography (MDCT). Open surgical treatment was applied. Endarterectomy of the left upper renal artery, perfusion of the right common bottom pole renal artery, and reimplantation of both bottom polar renal arteries were done. Isthmus was not divided. The coexistence of HSK and abdominal aortic aneurysm (AAA) is a rare condition. It presents a technical challenge to vascular surgeons because the surgical treatment of such an aneurysm is complicated due to the abnormal anatomy, difficulties in exposing the aneurysm, and a variable blood supply to the isthmus and lower poles of the HSK. Conclusion. Open surgical repair of AAA with HSK is a successful method and provides good exposure, the possibility of renal circulation preservation, and prevention of renal insufficiency.